EFEKTIVITAS PENGGUNAAN MEDIA SOSIAL PADA UMKM DAERAH ALIRAN SUNGAI (DAS) CITARUM, KARAWANG - Ria Estiana; Nurul Giswi Karomah; Teddy Setiady (POLITEKNIK LP3I JAKARTA, 2021)
This study aims to determine the correlation between the characteristics of followers and social media exposure on the effectiveness of promotion of MSME products carried out in the Citarum river basin, Karawang Regency through social media. The population in this study were the followers of MSME social media in 4 sub-districts in the Citarum Watershed, Karawang Regency. The sampling method used in this study is non-probability sampling and a sampling technique based on spontaneity, which means that anyone who accidentally meets their characteristics can be used as a sample (respondent). The results showed the Characteristics of Followers (X1) and Social Media Awareness (X2) had a sufficient and negative relationship, so the relationship between the two variables was that if the characteristics of followers were low, social media awareness was high and vice versa. Characteristics of Followers (X1) and Promotion Effectiveness (Y) have a strong and positive relationship. Chi square test is to see the relationship, so there is no relationship between Follower Characteristics and Promotion Effectiveness. The results of the spearman rank correlation analysis show that the correlation coefficient of Social Media Awareness (X2) and Promotion Effectiveness (Y) has a strong and positive relationship, so the relationship between the two variables is that if Social Media Awareness is high then the Promotion Effectiveness is high. Chi square testing is to see the relationship, so there is a relationship between Social Media Awareness and Promotion Effectiveness.Keyword: characteristics of followers,social media exposure, the effectiveness of promotion